Implementation Of The Policy Granting Minimarket Establishment Permits In Bandung City - H.R. Iip Hidajat; Yeti Rohayati; Tati Sarihati (Jurnal Scientia, 2024)
The implementation of the policy on granting permits for the establishment of minimarkets in the city of Bandung has not been fully implemented effectively. The theory used as a reference for analysis is policy implementation theory according to Mazmanian and Sabatier. According to Mazmanian and Sabatier, the success of implementing the policy of granting permits for the establishment of minimarkets in Bandung City is influenced by, whether problems are easy to control, the ability of wisdom to structure the implementation process, aspects outside the policy implementation process, the stages of the implementation process. This study was designed based on a qualitative approach with descriptive methods. Data collection techniques include interviews, observation, literature study/documentation. The informants were all interested parties, both from government officials and other stakeholders. Through a qualitative approach. Analysis is used by collecting, processing, analyzing, interpreting and drawing conclusions. This research results that, policy implementation which includes whether problems are easy to control, the ability of wisdom to structure the implementation process, aspects outside the policy implementation process, the stages of the implementation process, do not fully describe the implementation of the policy for granting permits for the establishment of minimarkets in Bandung City, thus From the findings, that Mazmanian and Sabatier's theory strengthens this research, however, because the implementation of the policy on granting permits to establish minimarkets is not yet in accordance with applicable regulations because the factor that most contributes to the implementation of the policy on granting permits to establish minimarkets is "The importance of feedback from the community in granting permits to establish Mini Market".